Atomic Cu Sites Engineering Enables Efficient CO2 Electroreduction to Methane with High CH4/C2H4 Ratio - Li, Minhan; Zhang, Fangzhou; Kuang, Min; Ma, Yuanyuan; Liao, Ting; Sun, Ziqi; Luo, Wei; Jiang, Wan; Yang, Jianping (Nano-Micro Letters, 2023)
Electrochemical reduction of CO2 into high-value hydrocarbons and alcohols by using Cu-based catalysts is a promising and attractive technology for CO2 capture and utilization, resulting from their high catalytic activity and selectivity. The mobility and accessibility of active sites in Cu-based catalysts significantly hinder the development of efficient Cu-based catalysts for CO2 electrochemical reduction reaction (CO2RR). Herein, a facile and effective strategy is developed to engineer accessible and structural stable Cu sites by incorporating single atomic Cu into the nitrogen cavities of the host graphitic carbon nitride (g-C3N4) as the active sites for CO2-to-CH4 conversion in CO2RR. By regulating the coordination and density of Cu sites in g-C3N4, an optimal catalyst corresponding to a one Cu atom in one nitrogen cavity reaches the highest CH4 Faraday efficiency of 49.04% and produces the products with a high CH4/C2H4 ratio over 9. This work provides the first experimental study on g-C3N4-supported single Cu atom catalyst for efficient CH4 production from CO2RR and suggests a principle in designing highly stable and selective high-efficiency Cu-based catalysts for CO2RR by engineering Cu active sites in 2D materials with porous crystal structures. Highlights: 1 The Cu-doped graphitic carbon nitride (g-C3N4) material is synthesized by an in situ thermal polymerization strategy, through which the atomic dispersion and coordination structure of Cu on g-C3N4 are realized by regulating the doping level of Cu. 2 High Faraday efficiency of CH4 of 49.04% and a maximum CH4/C2H4 ratio up to 35.03 are achieved for the first time on g-C3N4-supported Cu single-atom catalyst. 3 Structure–activity relationship analysis based on experimental and theoretical studies demonstrates the well-defined Cu single atoms coordinated with N atoms in the nitrogen cavity of g-C3N4 are active sites for CO2-to-CH4.